Health Benefits in a Cohort of Children 6 Months After Tonsil Surgery in Relation to the Perioperative Period: An Observational Prospective Cohort Study - Lundeberg Stefan; Elisabeth Ericsson (Health Science Reports)
ABSTRACT Background and Aim Tonsil‐surgery is a common treatment for tonsillitis and upper‐airway obstruction. Health benefits are a key point of clinical concern. Aim: To evaluate health benefits 6‐months after pediatric tonsil‐surgery and to examine the influence of the perioperative period on health‐related quality of life (HRQoL). Method Participants, 198 children (4–17 years) who underwent tonsillectomy ± adenoidectomy on infection‐related indications (TE ± Ainfec, n = 46), tonsillectomy ± adenoidectomy due to upper‐airway‐obstruction (TE ± Aobstr, n = 44), or tonsillotomy ± adenoidectomy due to upper‐airway‐obstruction (TT ± Aobstr, n = 108). Data were collected via a postoperative pain‐diary, and 6‐month‐questionnaires. The Glasgow Children's Benefit Inventory (GCBI) evaluated HRQoL. An additional questionnaire assessed disease‐specific benefits, including open‐ended‐questions to capture what the children wanted to convey to other children scheduled for surgery. Results QoL‐score after surgery was positive in all indication/surgical‐method groups. The highest GCBI‐scores were seen in the subscale‐scores for physical health and vitality. Comparing TE ± Aobstr and TT ± Aobstr, no significant differences were noted in the total‐score or in the subscores. No differences in GCBI‐scores were seen between subgroups of patients divided by postoperative pain intensity and duration. No differences in frequency or loudness of snoring or ENT‐infections were seen between the groups, and satisfaction rates were high. The information that the children considered essential to share with others covered details of the day of surgery, including the anesthesia, nutrition, pain and pain relief, and well‐being after surgery. Conclusions All indication/surgical‐method groups reported improvements regarding the health benefits of surgery, with the most pronounced effect being seen for physical health and vitality. TE ± A and TT ± A showed similar benefits in cases of obstructive and infection problems. Postoperative pain had no impact on QoL at the 6‐month follow‐up. Children's memories of the surgery can provide direction for management and improvements in children's care. Pain management needs to be optimized to improve recovery.